KESENJANGAN DESAIN KURIKULUM MERDEKA DALAM IMPLEMENTASI PEMBELAJARAN MATEMATIKA: TINJAUAN LITERATUR HAMBATAN DAN SOLUSI - Nuriyah, Dewi Sinta; Rohmah, Sayyidatur; Widya, Titan Zhafira; Hadi, Syaiful; Zahroh, Umy (Universitas Batanghari Jambi, 2026)
This study aims to analyze the gap between the design of the Independent Curriculum and its implementation in mathematics learning. Using the Systematic Literature Review (SLR) method, this study examined 16 articles published between 2021 and 2025 that met the inclusion criteria regarding obstacles and solutions in planning, implementing, and evaluating learning. The review results indicate that the greatest obstacles occur at the planning stage, including teachers' poor understanding of the Learning Objectives Flow (ATP), the development of teaching modules, and the role of teachers as facilitators. At the implementation stage, challenges arise in implementing differentiated learning, the use of technology-based media, and limited infrastructure. Meanwhile, at the evaluation stage, teachers still experience difficulties in implementing authentic, diagnostic, and formative assessments that meet the curriculum's demands. This study contributes by comprehensively mapping obstacles and offering solutions based on scientific findings, such as strengthening teacher competencies, optimizing learning communities, and providing supporting facilities. These findings emphasize the importance of a stronger educational ecosystem so that the Independent Curriculum can optimally achieve its goal of developing mathematics competencies.